2018
DOI: 10.3389/fvets.2018.00235
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Recovery From General Anesthesia Possibly Related to Persistent Hypoxemia in a Draft Horse

Abstract: Horses are susceptible to developing large areas of pulmonary atelectasis during recumbency and anesthesia. The subsequent pulmonary shunt is responsible for significant impairment of oxygenation. Since ventilation perfusion mismatch persists into the post-operative period, hypoxemia remains an important concern in the recovery stall. This case report describes the diagnosis and supportive therapy of persistent hypoxemia in a 914 kg draft horse after isoflurane anesthesia. It highlights how challenging it can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Our study also showed an increase in respiratory complications associated with heavy weight. Body weight as well as body shape influence arterial oxygenation and alveolar arterial oxygen gradient, increasing the risk of hypoxemia (27).…”
Section: Explanatory Factors For Respiratory Complicationsmentioning
confidence: 99%
“…Our study also showed an increase in respiratory complications associated with heavy weight. Body weight as well as body shape influence arterial oxygenation and alveolar arterial oxygen gradient, increasing the risk of hypoxemia (27).…”
Section: Explanatory Factors For Respiratory Complicationsmentioning
confidence: 99%
“…In this case the duration to standing was considerably longer than is typical at the present institution where most horses stand within 60 minutes. A recent case report about equine anaesthetic recovery suggested that hypoxaemia, residual drug effects and hypothermia may have contributed to a delayed recovery in a nine‐year‐old Boulonnais gelding 12. In the present case these factors were all considered but were deemed unlikely.…”
Section: Discussionmentioning
confidence: 77%
“…There is evidence that intraoperative hypoxaemia might prolong recovery [ 31 , 33 ] and have a negative effect on recovery quality [ 25 ], particularly in horses undergoing emergency laparotomy due to colic where intraoperative hypoxaemia increased fatality rate [ 31 ]. The present study did not find that intraoperative hypoxaemia affected recovery score, but the use of intraoperative salbutamol did.…”
Section: Discussionmentioning
confidence: 99%